Learning ActionScript 2.0 for Macromedia® Flash® 8 - DeHaan, Jen; DeHaan, Peter (Adobe Press, 2005)
Powerful development and design tools require thorough and authoritative technical advice and documentation. When it comes to Macromedia Flash, no one is more authoritative than Macromedia Development and writing teams. Now their official documentation is available to you in printed book form. As you work, keep this guide by your side for ready access to valuable information on using Flash. We've designed it so that it's easy to annotate as you progress. Learning ActionScript 2.0 for Macromedia Flash 8 shows you how to write proper ActionScript syntax to create useful and interactive Flash applications. This book includes examples of object-oriented programming, and teaches you how to write custom classes for your Flash applications. Learning ActionScript 2.0 for Macromedia Flash 8 also includes numerous hands-on examples on how to apply expressive and interactive features to your files using ActionScript code, such as file upload, filter effects, scripted animation, and anti-alias text using the FlashType font rendering engine. In Learning Actionscript 2.0 for Macromedia Flash 8, learn how to: - Write proper ActionScript syntax using the fundamentals of the ActionScript language. - Use object-oriented programming techniques to build Flash applications. - Use ActionScript classes to add interactivity and expressive features to your Flash applications. - Use best practices and coding conventions to optimize, structure, and write consistent ActionScript.
Keywords: ActionScript (Computer program language); ActionScript (Langage de programmation)